Regulatory T cells from IL-10-deficient mice fail to suppress contact hypersensitivity reactions due to lack of adenosine production - Ring, Sabine; Enk, Alexander; Mahnke, Karsten (The journal of investigative dermatology, 2011)
CD4+CD25+Foxp3+ regulatory T cells (Tregs) produce immunosuppressive adenosine by degradation of adenosine triphosphate (ATP) by the ectonucleotidases CD39 and CD73. In this sequence of events, ATP is not only the substrate for generation of adenosine but it also activates the immunosuppressive functions of Tregs. To compare the effects of ATP on IL-10-deficient (IL-10−/−) Tregs with wild-type (wt) Tregs, we incubated both types of Tregs with ATP and assessed their phenotype and function. We show that IL-10−/− Tregs failed to become activated by ATP and were impaired in adenosine production. As a consequence, IL-10−/− Tregs were unable to block adherence of effector T cells to the endothelium in vitro. When testing the signaling of the ATP receptor P2X7 in IL-10−/− Tregs, we recorded no elevation of intracellular calcium after engagement of P2X7 receptors, as compared with wt Tregs, thus indicating that IL-10−/− Tregs fail to react normally to ATP and display impaired adenosine production, which explains their inability to suppress contact hypersensitivity responses. Therefore, when using IL-10−/− Tregs in different disease models, one has to take into account that adenosine production is abrogated and reduced suppressive effects may not be exclusively attributable to the lack of IL-10 production.
published online 24 March 2011; version of record 8 December 2015
Gesehen am 16.09.2022